RECASTING THE NATURALISM–NORMATIVITY DEBATE: NEUROSCIENCE, NEUROPHILOSOPHY, NEUROETHICS - Oliveira, Nythamar de (Princípios: Revista de Filosofia (UFRN), 2015)
Assuming that there is a "neuroscientific turn" in moral philosophy, I will be discussing in this paper how neurophilosophy could shed light on the normative problems raised by a naturalistic project of ethical and social research, particularly related to the question of the articulation between the biological evolution of human species and the social and historical evolution of society and social groups. Taking a critical approach to naturalism and normative theories, I argue that there is a neurophenomenological deficit in naturalism (particularly in the versions of naturalism that follow the program of a naturalized epistemology) and in the normative theories (particularly in the critical theory) and I put forward a version of social constructivism that combines the neuroscientific and neurophilosophical models of Antonio Damasio and Jesse Prinz.